Strategi Pemasaran Meningkatkan Volume Penjualan Produk Pada PT. Indomarco Adi Prima Sub DC Pamekasan - Mufidah, Diana; Syarif, Muh. (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This study aims to determine marketing strategies in increasing product sales volume at PT. Indomarco Adi Prima Sub DC Pamekasan. The approach used in this research is qualitative, through interviews and direct observation. using the SWOT analysis technique. The results of the research show that the marketing strategy carried out by PT. Indomarco Adi Prima has carried out the strategy appropriately and correctly and the SWOT analysis calculations listed in the carteseus diagram show that PT. Indomarco Adi Prima is in quadrant 1 position, namely growth where the company can develop, maintain and improve the quality of existing products so that people continue to trust PT. Indomarco Adi Prima products. The recommended strategy that can be implemented by PT. Indomarco is a growth oriented strategy, meaning that PT. Indomarco's sales strategy is in good condition so that it is possible to continue to expand, enlarge or widen the target market and achieve progress by taking advantage of the strengths and opportunities possessed by PT. Indomarco Adi Prima Sub DC Pamekasan.